Efek Pandemi Covid-19 Terhadap Kejahatan Siber di Indonesia - Warsino Warsino (Program Studi Teknik Industri Universitas Setia Budi, 2020)
Crime occurs not only by intention, but also because there is an opportunity. The Covid-19 pandemic impact on all aspects of human life. All activity that usually done outside. because of the pandemic, should be done inside of house. The increasing use of internet by public, coupled with the lack of awareness to computer security making this chance exploited by the cybercriminals. As the result, the cyber attack is increasing not only in Indonesia, but also all over the world. As of April 2020, there has been a compulsive increase of 88,414,296 attacks, with the dominance of Trojan attacks as much as 56%, Information gathering by 43% and Web Attack by 1%. Therefore, the understanding and awareness are required from all internet users to close the gap security, so that the public can work safely, calmly, and comfortably from home.